2017
DOI: 10.1007/s10461-017-1736-3
|View full text |Cite
|
Sign up to set email alerts
|

Drug Use and Sexual HIV Transmission Risk Among Men Who have Sex with Men and Women (MSMW), Men Who have Sex with Men only (MSMO), and Men Who have Sex with Women Only (MSWO) and the Female Partners of MSMW and MSWO: A Network Perspective

Abstract: We described drug use, sex risk, and STI/HIV among men who have sex with men and women (MSMW) and their female partners. We used the Network, Norms and HIV/STI Risk among Youth (NNAHRAY) study to evaluate drug use, sex risk, and biologically-confirmed STI/HIV in (1) MSMW and men who had sex with men only (MSMO) versus men who had sex with women only (MSWO) and (2) female partners of MSMW versus female partners of MSWO (N=182 men, 152 women). MSMW vs. MSWO had 30 to 60% increased odds of substance use, over twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
2
5
1
Order By: Relevance
“…Our finding about MSMW having fewer oral male sex partners than MSMO is contrary to previous studies where MSMW reported commonly occurring oral sex with both men and women, but those reports had small sample sizes and no comparative group of MSMO [20,21]. Additionally, results showing that similar percentages of MSMW and MSMOengaged in condomless anal sex in the past 12 months is also inconsistent with the literature [12].…”
Section: Discussioncontrasting
confidence: 99%
“…Our finding about MSMW having fewer oral male sex partners than MSMO is contrary to previous studies where MSMW reported commonly occurring oral sex with both men and women, but those reports had small sample sizes and no comparative group of MSMO [20,21]. Additionally, results showing that similar percentages of MSMW and MSMOengaged in condomless anal sex in the past 12 months is also inconsistent with the literature [12].…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, a spillover between FSW and PWID likely occurred (2/5 FSW were placed in PWID cluster) (Figure 3). A spillover between FSW and PWID increased the risk of HIV transmission in the general population (de Oliveira et al, 2017;Dyer et al, 2017;Li et al, 2018;Paraskevis et al, 2018). A similar finding was observed in this study with a cluster of the general population; PWID, sex worker, and clients of the sex worker may result from this spillover and occur through the sexual transmission of HIV.…”
Section: Discussionsupporting
confidence: 87%
“… 25 In the USA, MSMW had a 57% increased odds of having an STI compared with heterosexuals, but no differences were found between MSMO and heterosexuals or MSMO and MSMW. 24 Similarly, an Indian study has shown that there were no differences in any STI positivity (ie, either syphilis, gonorrhoea or chlamydia) between MSMO and MSMW. 23 Furthermore, MSMW are also less likely to ever have an HIV/STI test compared with MSMO, 23 26 27 which is consistent with an Australian qualitative study suggesting MSMW have a poor sexual health knowledge compared with MSMO.…”
Section: Discussionmentioning
confidence: 96%